6 - The Private Higher Education Sector in Africa: Current Trends and Themes in Six Country Studies - Thaver, Beverley (Journal of Higher Education in Africa, 2008)
In Africa, the phenomenon of access to public higher education is under much pres- sure, and is harnessed by (among others) two privatization forces. These refer to the retreat of the state in terms of the provisioning of public higher education and the global economic rush which have culminated in both an increase in the number and to some extent the range of private higher education institutional types offering diverse course offerings. Although still small in scale and not representing a domi- nant share of higher education enrolment, their existence signals that they are meet- ing a social function of access in Africa, albeit limited. In light of this, there are traces of course offerings that suggest a small alignment with the economic and social needs of a modern society. Caught between the interstices of global eco- nomic capital and national societal functions, these institutions’ mandates and iden- tities are beginning to be stretched to meet modern imperatives. But, in this vortex, they are simultaneously hamstrung by certain sustainable systemic elements that go against the grain of the requirements for traditional higher education. Following this line of argument, the article begins with an overview of six country studies in Africa, including an outline of some of the discursive trends. It concludes by pro- viding a snapshot glimpse into the private higher education sector in South Africa.